Pengaruh Brand Image, Halal Awareness dan Islamic Branding Terhadap Loyalitas Merek Pada Skincare Wardah - usnan, Usnan; Mustika, Dama; Mahmudah Dariati, Anis (Fakultas Bisnis Universitas Mikroskil, 2024)
This research discusses the influence of brand image, halal awareness and Islamic branding on brand loyalty among muslim consumers. This research aims to understand how these three variables interact and influence consumer decisions to remain loyal to a brand, particularly in the context of sharia based products. The method used is a quantitative approach with data collection through questionnaires distributed to consumers who use halal labeled products. The research population is the entire muslim community spread across cities in riau province. Convenience sampling is a type of sample where respondents are obtained randomly totaling 200 respondents. Research results show that a good integration of halal awareness can positively enhance brand loyalty, as consumers feel that halal awareness aligns with their personal and religious values. Unlike brand image and Islamic branding is not well integrated with brand loyalty. This research identifies gaps in the existing literature regarding the simultaneous influence of the three variables, with a significance value of 0.000.